Efficacy and safety of flow diverters in basilar artery aneurysms: a single-center retrospective cohort study - Huang, Ziyuan; Chen, Chuan; Zhang, Baoyu; Hu, Yuanjun; Wang, Hui; Ling, Cong (Frontiers in Neurology, 2025)
ObjectiveTo evaluate the efficacy and safety of flow diverter (FD) devices in the treatment of basilar artery aneurysms, and to assess their clinical outcomes and associated complications.MethodsA retrospective analysis was conducted on 30 patients with basilar artery aneurysms treated with FD devices at our institution between 2020 and 2024. Patient demographics, aneurysm characteristics, intraoperative and postoperative imaging, and clinical follow-up data were collected. Statistical analysis was performed to assess treatment efficacy and complication rates.ResultsAmong the 30 patients, 20 were male (66.7%) and 10 were female (33.3%), with a median age group of 65–69 years. The majority of aneurysms were located in the basilar artery trunk (70%), while 30% were basilar apex aneurysms. All procedures were technically successful (success rate: 100%). The mean aneurysm diameter was 10.6 ± 4.9 mm. The mean follow-up period was 12.9 months. Imaging follow-up demonstrated a complete or near-complete aneurysm occlusion rate of 86.7%; occlusion rates for the Tubridge and Pipeline Flex devices were 83.3 and 88.9%, respectively, with no statistically significant difference between the two devices (p > 0.05). Treatment-related complications occurred in 4 cases (13.3%), all presenting as transient ischemic symptoms, with no cases of permanent severe neurological deficits. 93.3% of patients (28/30) achieved an excellent functional outcome (mRS score of 0–1), and all patients (100%) had a functional outcome of mRS 0–2.ConclusionIn this retrospective cohort, FD treatment for basilar artery aneurysms was associated with a high rate of complete or near-complete occlusion (86.7%) and a favorable safety profile, as evidenced by the low rate of complications (13.3%, all transient). The clinical outcomes were excellent, with 93.3% of patients achieving an mRS of 0–1. The Tubridge and Pipeline devices demonstrated comparable efficacy and safety outcomes in this study, although the small sample size and non-randomized design preclude definitive conclusions regarding superiority or equivalence. Our findings indicate that rigorous preoperative antiplatelet management and meticulous operative technique are critical for these results. This study supports the consideration of FDs for BAAs in carefully selected patients, but further large-scale, prospective studies are warranted to confirm long-term durability and optimize patient selection.